The Impact of Tax, Foreign Ownership, and Firm Size on Transfer Pricing (Empirical Studies on Coal Mining Sub-Sector Companies Listed in Indonesia Stock Exchange for 2012-2021 Period) - Vania Audrey Alexandria; Wirawan Endro Dwi Radianto (Politeknik Negeri Bengkalis, 2023)
This study aims to examine the effect of tax, foreign ownership, and company size on transfer pricing in coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2012-2021 period. Based on the purposive sampling method, 19 companies met the criteria to be sampled in the research from 2012-2021. The number of samples in the study for 10 years with 157 observations. This study uses a robust regression analysis model. Based on the results of data analysis research, it can be concluded that taxes have a positive effect on transfer pricing, while foreign ownership and company size have no effect on transfer pricing in coal mining sub-sector companies listed on IDX for the 2012-2021 period.